Wireless, Programmable, and Refillable Hydrogel Bioelectronics for Enhanced Diabetic Wound Healing - Ningjie Du; Yunlong Fan; Yunting Zhang; Hao Huang; Yidan Lyu; Ruisi Cai; Yuqi Zhang; Tianyuan Zhang; Yixin Guan; Kewang Nan (Advanced Science)
Abstract Diabetic wounds, characterized by complex pathogenesis and high infection rates, pose significant challenges in treatment due to prolonged recovery times and high recurrence rates, often leading to severe complications such as amputation and death. Traditional dry dressing treatments fail to address the unique microenvironment of diabetic wounds and tend to cause secondary damage due to frequent replacement. In this study, an electronic‐embedding, drug‐loading hydrogel bioelectronics is reported for accelerating diabetic wound healing using a combination of programmable pharmaceutical and electrostimulative approaches. Encapsulated in stretchable and biocompatible materials, this device is capable of multiple drug refilling and accelerated drug release modulated by on‐board electronics. In vivo experiments on diabetic model rats confirm the device's effectiveness in promoting wound healing. This innovative approach implies the potential for improving diabetic wound management using a combination of physical, material, and pharmaceutical interventions.